Efeito da atorvastatina no tecido ósseo de ratas submetidas a osteonecrose de maxilares induzida por ácido zoledrônico - Ferreira, Vanessa Costa de Sousa (2018)
Bisphophonate-related osteonecrosis of the jaw (BRONJ) is defined as exposed bone that has persisted for than 8 weeks after the use of bisphophonate and without history of radiation therapy or metastatic disease. Despite the physiopathological mechanism are yet to be understood, inflammation, vascular problems and bone turnover supression seem to play a role on this condition. In this way highlights Atorvastatin (ATV), an hypolipemiant agent, that also presents importante pleiotropic effects: anti-inflammatory, angiogenic and bone anabolic. In this contexto, the aim of this study was to evaluate the effect of ATV over que morphofunctional aspects of bone tissue on animais subjected to BRONJ. For this, it was used 72 female Wistar rats (180-220 g), divided in 4 groups: Saline (SAL), Zoledronic Acid (ZA); ATV pre (ATV - PRÉ) or post-operatory (ATV - PÓS). BRONJ was induced by administration of 0.1 mg/kg of AZ, (i.p.) 3x/wk for 9 weeks. The animals from SAL group received 0.1 ml of 0.9% saline solution (i.p.) for the same period. On day 42 (D42) all animals had the 3 left superior molars extracted. ATV was administered at 27 mg/kg (v.o.) daily for 3 weeks pre-operatory (D21-D42) or post-operatory (D42-D77). These animals were followed daily and euthanized on D77 ou week 11 (W11). Maxillae were removed for macroscopic, histopathological and histometric analyses, scanning electron microscopy (SEM), bone-filling percentage analysis using confocal microscopy, collagen analysis by picrosirius red staining under polarized light and immunohistochemistry for DKK-1, Wnt 10b, β- catenin and caspase-3. The gingival tissue was colleted for TNF-α e IL-1β quantification, and the blood samples were collected to biochemical dosage. The treatment with ATV reduced the intensity of the inflammatory process, as well as the presence of bone sequesters, increased the number of osteocytes and reduced the number of empty lacunae, compared to ZA (p<0.05). ATV kept the regular topography on SEM analysis, compared to ZA. ATV (PRE and POS) increased bone- filling and type I-collagen percentage and reduced III-collagen percentage (p<0.05), reduced immunolabelling Caspase-3, and increased immunolabelling for Wnt10b and β-catenin, reduced the gingival levels of IL-1β (ATV – PRE and ATV - POS) and TNF (ATV - POS), compared to ZA (p<0.05). On Raman, it was observed an increase on all bands as well as on mineral/matriz ratio on ATV-PRE and ATV-POS groups, when compared to ZA (p<0,05).The treatment with ATV lowered the serum levels of Calcium, and raised seric Phosphorus as well as Bone-specific alkaline phosphatase compared to ZA (p<0.05). In summary, the findings of this study showed that ATV presented anti-inflammatory activity and anti-resorptive effect as well as kept bone vitality, metabolism and structure, which can be an interesting pharmacological tool as adjuvant to BRONJ therapy.